Effects of calcium carbonate on preparation and mechanical properties of wood/plastic composite - Hongzhen, Cai; Keyan, Yang; Weiming, Yi (International Journal of Agricultural and Biological Engineering, 2017)
In order to reduce the cost and improve the performance of wood/plastic composite (WPC), the effects of additive amount of calcium carbonate on preparation and mechanical properties of high density polyethylene (HDPE) based WPC were studied. The results showed that the calcium carbonate can improve preparation and mechanical properties effectively. The 20% calcium carbonate additive could effectively improve the melt fluidity of the composites and reduce the energy consumption in the processing. The calcium carbonate had a favorable toughening effect on polymer and was effectively filled in WPC. For the best tensile, flexural and impact properties of WPC, the appropriate additive amounts of calcium carbonate were 25%, 10% and 30%, respectively. The additive amount for preparation of WPC should be based on the processing requirements and the demands for different working conditions. Keywords: wood/plastic composite, calcium carbonate, preparation, mechanical property, fluidity, SEM DOI: 10.3965/j.ijabe.20171001.2707 Citation: Cai H Z, Yang K Y, Yi W M. Effects of calcium carbonate on preparation and mechanical properties of wood/plastic composite. Int J Agric & Biol Eng, 2017; 10(1): 184–190.